2009
DOI: 10.1111/j.1365-2745.2009.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic plants as facilitators: more Dryad than Dracula?

Abstract: Summary1. Despite being components of most vegetation types, the community-level effects of parasitic plants are often ignored. The few studies adopting a broader view have revealed that these plants mediate a series of direct and indirect competitive and facilitative effects on community structure and ecosystem processes. 2. I summarize findings from the two best-studied systems: a set of experimental and manipulative studies from northern Sweden and an integrated research programme in southern Australia, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 71 publications
(139 reference statements)
3
91
1
1
Order By: Relevance
“…So, rather than structural complexity driving diversity, it is nutrient enrichment driving small-scale heterogeneity and thereby promoting coexistence, consistent with work on other parasitic groups [5]. These nutrients are partly reallocated from the host by the parasite but are also imported from further afield, deposited by visiting animals (the dryad hypothesis [6]). …”
supporting
confidence: 62%
“…So, rather than structural complexity driving diversity, it is nutrient enrichment driving small-scale heterogeneity and thereby promoting coexistence, consistent with work on other parasitic groups [5]. These nutrients are partly reallocated from the host by the parasite but are also imported from further afield, deposited by visiting animals (the dryad hypothesis [6]). …”
supporting
confidence: 62%
“…Through the parasitism pathway strong parasites reduce host growth, which in turn alters diversity and reduces community productivity. However, hemiparasites tend to concentrate nutrients in leaves, which increases litter decomposition and nutrient release (Quested et al 2002(Quested et al , 2003Watson 2009). Through the alternative litter pathway, hemiparasites increase nutrient availability in the community, leading to little change in diversity and increased community productivity.…”
Section: (B)mentioning
confidence: 99%
“…However, recent research has shown that aerial hemiparasites (hereafter mistletoes) that occur in tree canopies can alter litterfall, decomposition rates, and soil microbial communities beneath the canopies of their hosts (Press, 1998;Watson, 2009). Consequently, mistletoes have potential to alter nutrient cycling rates, and thus may contribute to nutrient enrichment in tree-dominated patches.…”
Section: Introductionmentioning
confidence: 99%